Corticostriatal functional interactions in Parkinson’s disease: a rTMS/[(11)C]raclopride PET study - Strafella, Antonio P. (2005)
Several animal studies have shown that striatal dopamine can be released under direct control of glutamatergic corticostriatal efferents. In Parkinson’s disease (PD), abnormalities in corticostriatal interactions are believed to play an important role in the pathophysiology of the disease. Previously, we have reported that, in healthy subjects, repetitive transcranial magnetic stimulation (rTMS) of motor cortex (MC) induces focal dopamine release in the ipsilateral putamen. In the present study, using [(11)C]raclopride PET, we sought to investigate early PD patients with evidence of unilateral motor symptoms. We measured in the putamen changes in extracellular dopamine concentration following rTMS (intensity, 90% of the resting motor threshold; frequency, 10 Hz) of the left and right MC. The main objective was to identify potential differences in corticostriatal dopamine release between the hemisphere associated with clear contralateral motor symptoms (symptomatic hemisphere) and the presymptomatic stage of the other hemisphere (asymptomatic hemisphere). Repetitive TMS of MC caused a binding reduction in the ipsilateral putamen of both hemispheres. In the symptomatic hemisphere, while the amount of TMS-induced dopamine release was, as expected, smaller, the size of the significant cluster of change in [(11)C]raclopride binding was, instead, 61.4% greater than in the asymptomatic hemisphere. This finding of a spatially enlarged area of dopamine release, following cortical stimulation, may represent a possible in vivo expression of a loss of functional segregation of cortical information to the striatum and an indirect evidence of abnormal corticostriatal transmission in early PD. This has potential implications for models of basal ganglia function in PD.